2020
DOI: 10.1002/chem.202003133
|View full text |Cite
|
Sign up to set email alerts
|

Linking of CuI Units by Tetrahedral Mo2E2 Complexes (E=P, As)

Abstract: The reaction of [Cp 2 Mo 2 (CO) 4 (m,h 2:2-E 2)] (A:E= P, B:E = As, Cp = C 5 H 5)w ith the WCA-containing Cu I salts ([Cu(CH 3 CN) 4 ][Al{OC(CF 3) 3 } 4 ](CuTEF, C), [Cu(CH 3 CN) 4 ][BF 4 ] (D)a nd [Cu(CH 3 CN) 3.5 ][FAl{OC 6 F 10 (C 6 F 5)} 3 ](CuFAl, E)) affords seven unprecedented coordination compounds. Depending on the E 2 ligand complex, the counter anion of the coppers alt and the stoichiometry,f our dinuclear copper dimers and three trinuclearc opper compounds are accessible. The latter complexes revea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…According to the CSD database, [16] η 2 ‐coordination mode of E was also observed in four compounds, namely [( E )(μ‐CuX)] 2 (X=Cl, Br), [( E )(μ‐CuI 2 )] ∞ and [Cu 2 (η 2 ‐ E )(η 2 : 1 ‐ E ) 3 ][GaCl 4 ] 2 . 12a] Note that the only example of η 2 ‐side‐on coordinated D was observed in [(MeCN) 2 Cu 2 {(μ,η 2 : 2 ‐( D )} 2 )(Cu){μ,η 2 : η 2 : η 1 : η 1 ‐( D ) 2 }][BF 4 ] 3, [12d] which is why 4 represents only the second example to date. Both the E−E bond distances found in 4 (As1‐As1’ 2.3808(2) Å) and 5 (Sb1–Sb2: 2.75039(13) Å) are longer than that of free D and E , but comparable to the related compounds shown in Chart 1.…”
Section: Resultsmentioning
confidence: 99%
“…According to the CSD database, [16] η 2 ‐coordination mode of E was also observed in four compounds, namely [( E )(μ‐CuX)] 2 (X=Cl, Br), [( E )(μ‐CuI 2 )] ∞ and [Cu 2 (η 2 ‐ E )(η 2 : 1 ‐ E ) 3 ][GaCl 4 ] 2 . 12a] Note that the only example of η 2 ‐side‐on coordinated D was observed in [(MeCN) 2 Cu 2 {(μ,η 2 : 2 ‐( D )} 2 )(Cu){μ,η 2 : η 2 : η 1 : η 1 ‐( D ) 2 }][BF 4 ] 3, [12d] which is why 4 represents only the second example to date. Both the E−E bond distances found in 4 (As1‐As1’ 2.3808(2) Å) and 5 (Sb1–Sb2: 2.75039(13) Å) are longer than that of free D and E , but comparable to the related compounds shown in Chart 1.…”
Section: Resultsmentioning
confidence: 99%
“…Current approaches in supramolecular chemistry focus on the use of nitrogen-, oxygen-, and/or sulfur-containing organic linkers to connect different metal centers. During the last decades, our group has demonstrated that organometallic E n (E = heavier group 15 element) ligand complexes are excellent building blocks for supramolecular assemblies as well . Indeed, many examples of the coordination chemistry of E n ( n = 1–6) ligand complexes toward coinage metal salts, also in combination with organic linkers, were reported during the past two decades. , This novel approach allowed the synthesis of a large library of aggregates including polymeric (1D, 2D , and 3D coordination polymers) and discrete (monomeric, dimeric or spherical aggregates as well as nanobowls) supramolecular assemblies. While the coinage metal salts of Cu I /Ag I /Au I have already been extensively utilized in these studies, the monovalent ions of the heavier group 13 elements, namely In I and Tl I , have only recently attracted general interest within the field of supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Indeed, many examples of the coordination chemistry of E n ( n = 1–6) ligand complexes toward coinage metal salts, also in combination with organic linkers, were reported during the past two decades. 6 , 7 This novel approach allowed the synthesis of a large library of aggregates including polymeric (1D, 8 10 2D 11 , 12 and 3D 13 coordination polymers) and discrete (monomeric, 14 dimeric 15 or spherical aggregates 16 18 as well as nanobowls 19 ) supramolecular assemblies. While the coinage metal salts of Cu I /Ag I /Au I have already been extensively utilized in these studies, the monovalent ions of the heavier group 13 elements, namely In I and Tl I , have only recently attracted general interest within the field of supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%